2018
DOI: 10.1002/app.46419
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and performance of poly(vinylidene fluoride) flat sheet membranes: Thermodynamic and kinetic aspects

Abstract: In this study, poly(vinylidene fluoride) (PVDF) membranes were prepared using two different solvents with various polymer concentrations to investigate the predominant kinetic or thermodynamic aspects of membrane preparation in a phase separation process. For this purpose, dimethyl sulfoxide (DMSO) as a weak solvent and N‐2‐methylpyrrolidone (NMP) as a strong solvent were used with polymer concentrations between 8 and 15 wt %. Scanning electron microscopy and water content, contact angle, and pore size measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It can be correlated to the combination effects of thermodynamic and kinetic of the polymer solution. An instable thermodynamic condition can generate an open structure with large finger‐like morphology whereas enhancement of the polymer solution viscosity (kinetic effect) can result in a sponge‐like morphology (Enayatzadeh & Mohammadi, 2018). From Figure 5a, by addition of sPEEK into the solution, a more open structure with larger finger‐likes was produced in the membrane medium.…”
Section: Resultsmentioning
confidence: 99%
“…It can be correlated to the combination effects of thermodynamic and kinetic of the polymer solution. An instable thermodynamic condition can generate an open structure with large finger‐like morphology whereas enhancement of the polymer solution viscosity (kinetic effect) can result in a sponge‐like morphology (Enayatzadeh & Mohammadi, 2018). From Figure 5a, by addition of sPEEK into the solution, a more open structure with larger finger‐likes was produced in the membrane medium.…”
Section: Resultsmentioning
confidence: 99%
“…Although the experimental points of the four systems studied appeared very proximate at 293 K the position of the cloud points were significantly different between solvents (i.e., PVDF/DMAc/water vs. PVDF/NMP/water and PES/DMAc/water vs. PES/NMP/water) and between polymers (i.e., PVDF/DMAc/water vs. PES/DMAc/water and PVDF/NMP/water vs. PES/NMP/water). Cloud point experimental data obtained between 293 and 295 K (room temperature) are widely reported in the literature for the four systems studied [ 7 , 14 , 28 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Experimental results of this study fall within the range of results previously reported at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results of this study fall within the range of results previously reported at room temperature. However, it is remarkable the huge dispersion of data reported for PVDF systems, especially in the PVDF/NMP/water system [ 41 , 44 ]. A relationship between the different polymer molecular weight characteristics of the polymers used in these studies with the variation of the cloud points reported was not found.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Marino et al [ 29 ], prepared a composite based on polyethersulfone (PES) by phase separation using a pleasant-smelling version of DMSO. Moreover, Enayatzadeh et al [ 31 ] and Arefi–Oskoui et al [ 32 ], reported thermodynamic and kinetic studies and the influence of different variables amount of PVDF on the physicochemical properties of the composite.…”
Section: Experimental Methodsmentioning
confidence: 99%